2012
DOI: 10.3892/ol.2012.991
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the phosphoinositide 3-kinase/Akt pathway in apoptosis induced by capsaicin in the human pancreatic cancer cell line PANC-1

Abstract: Abstract. Capsaicin, one of the major pungent ingredients found in red peppers, has been recently demonstrated to induce apoptosis in various malignant cell lines through an unclear mechanism. In this study, the effect of capsaicin on proliferation and apoptosis in the human pancreatic cancer cell line PANC-1 and its possible mechanism(s) of action were investigated. The results of a Cell Counting Kit-8 (CCK-8) assay revealed that capsaicin significantly decreased the viability of PANC-1 cells in a dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…To examine how sensory neurons impact PDAC initiation and progression, we first determined if neonatal capsaicin had direct effects on pancreatic cells because previous studies using cancer-derived cell lines showed it affected apoptosis and proliferation (28)(29)(30)(31)(32)(33)(34). The neurotoxic effects of neonatal capsaicin treatment are assumed to be via binding to TRPV1, the vanilloid receptor specific for capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…To examine how sensory neurons impact PDAC initiation and progression, we first determined if neonatal capsaicin had direct effects on pancreatic cells because previous studies using cancer-derived cell lines showed it affected apoptosis and proliferation (28)(29)(30)(31)(32)(33)(34). The neurotoxic effects of neonatal capsaicin treatment are assumed to be via binding to TRPV1, the vanilloid receptor specific for capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…Capsaicin at 5 mg/kg administered by oral gavage 3 days a week reduced 30 % the volume and weight of pancreatic tumors (Pramanik and Srivastava 2012;Zhang et al 2013) and urinary bladder tumors . Capsaicin was an extremely effective inhibitor of the cancer process, inducing apoptosis in cancer cells.…”
Section: In Vivo Antitumoral Action Of Capsaicinmentioning
confidence: 99%
“…Several reports indicate that capsaicin exerts its inhibitory effect on proliferation of pancreatic cancer cells via ERS-mediated apoptotic pathway or the phosphoinositide 3-kinase/Akt pathway [55] [58]. Other studies elucidated that capsaicin causes ROS generation through mitochondria and depleted intracellular antioxidants resulting in mitochondrial damage and apoptosis in pancreatic cancer cells, while normal pancreatic epithelial cells were resistant to the effects of capsaicin [59].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Capsaicin, the active compound in chili peppers, has been proven to induce apoptosis in various tumors so as to enhance the therapeutic effects of chemotherapy in pancreatic cancer [55]- [57]. Several reports indicate that capsaicin exerts its inhibitory effect on proliferation of pancreatic cancer cells via ERS-mediated apoptotic pathway or the phosphoinositide 3-kinase/Akt pathway [55] [58].…”
Section: Pancreatic Cancermentioning
confidence: 99%